Exploring the use of brain-sensing technologies for natural interactions - Pike, Matthew (2017)
Recent technical innovation in the field of Brain-Computer Interfaces (BCIs) has increased the opportunity for including physical, brain-sensing devices as a part of our day-to-day lives. The potential for obtaining a time-correlated, direct, brain-based measure of a participant's mental activity is an alluring and important development for HCI researchers.